(LIQUID PLUS LIQUID) EQUILIBRIA OF SOME (WATER PLUS TETRAHYDROFURAN PLUS SOLVENT) TERNARIES AT THE TEMPERATURE (293.2+/-0.1) K AND PRESSURE (101.3+/-0.7) KPA - (:unkn) unknown (ACADEMIC PRESS (LONDON) LTD, 1995)
Solubility curve and tie-line determinations for (water + tetrahydrofuran + cyclohexyl ethanoate), (water + tetrahydrofuran + 1,2-dichloroethane), (water + tetrahydrofuran + cyclohexanone), (water + tetrahydrofuran + 1-octanol), and (water + tetrahydrofuran + phenylmethanol) ternaries at the temperature (293.2 +/- 0.1) K and pressure (101.3 +/- 0.7) kPa are reported. A selectivity diagram on a solvent-free basis was used as comparative performance tests for the investigated extracting agents. It was found that cyclohexyl ethanoate represents the best performance among the studied solvents, if a high-boiling separating agent is to be considered.